Itaconate transport across the plasma membrane and Salmonella-containing vacuole via MCT1/4 modulates macrophage antibacterial activity - Meng, Qingcai; Li, Chengxi; Cai, Yuping; Chen, Ying; Chen, Xiaoqing; Wang, Xin; Zhang, Biling; Zhang, Yue; Liu, Feng; Chen, Meixin (浪淘沙预印本平台, 2025)
Itaconate accumulates and manifests antibacterial activity in macrophages upon bacterial infection. Convincing evidence substantiates that itaconate transports across the plasma membrane and vacuolar membrane. But the molecular bases underlying the bidirectional transport of itaconate across membranes and how it affects intracellular bacterial replication remain elusive. Here, we identify MCT1 and MCT4 as bidirectional transporters of itaconate. In addition to modulating itaconate concentration as transporters at the plasma membrane, MCT1 and MCT4 function as itaconate transporters at Salmonella-containing vacuole (SCV). Upon Salmonella infection, MCT1 and MCT4 transport itaconate into SCV facilitated by RAB32. Itaconate is also secreted out of cells through MCT1 and MCT4 as the infection persists. The suppression of MCT1 and MCT4-dependent itaconate secretion generally increases the concentration of itaconate and the prevalence of itaconate-targeted Salmonella intracellularly, consequently inhibiting Salmonella replication. Our study offers valuable insights into itaconate transport during bacterial infection and sheds light on the development of itaconate-dependent therapeutic strategies.